Expatriate performance in terrorism-endangered countries: The role of family and organizational support. Issue 5 (October 2015) - Bader, Benjamin; Berg, Nicola; Holtbrügge, Dirk
Highlights Business in terrorism-endangered countries is increasingly important. Assigning expatriates in these countries often is also a "family matter". Expatriates suffering from safety-related family tensions perform worse. POS is an appropriate measure to diminish negative effects.